Forestry in China : historical transitions and industry developments - Zhou, Shengxian (Gale virtual reference library, 2006)
Presents the current state of China's forestry industry. Explains that the transition from a focus on timber production to ecological development is inevitable, and a major breakthrough for forestry development in China.